2021
DOI: 10.34197/ats-scholar.2020-0154in
|View full text |Cite
|
Sign up to set email alerts
|

An International Virtual COVID-19 Critical Care Training Forum for Healthcare Workers

Abstract: Background: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic resulted in redeployment of non–critical care–trained providers to intensive care units across the world. Concurrently, traditional venues for delivery of medical education faced major disruptions. The need for a virtual forum to fill knowledge gaps for healthcare workers caring for patients with coronavirus disease (COVID-19) was apparent in the early stages of the pandemic. Objective: The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The content related to all aspects of critically ill COVID-19 patient care, including inpatient and post-intensive care management. [77] Faced with surges in demand due to the pandemic and the ensuing pressure on ICU facilities around the world, both C19_SPACE and CCCTF training programs demonstrated that medical education can be successfully delivered globally and virtually in times of crisis. [76] , [77] The reliance on video conferencing during the pandemic created new opportunities for interface between academic institutions and the broader medical community.…”
Section: Training Agenda In Icmmentioning
confidence: 99%
See 1 more Smart Citation
“…The content related to all aspects of critically ill COVID-19 patient care, including inpatient and post-intensive care management. [77] Faced with surges in demand due to the pandemic and the ensuing pressure on ICU facilities around the world, both C19_SPACE and CCCTF training programs demonstrated that medical education can be successfully delivered globally and virtually in times of crisis. [76] , [77] The reliance on video conferencing during the pandemic created new opportunities for interface between academic institutions and the broader medical community.…”
Section: Training Agenda In Icmmentioning
confidence: 99%
“… [77] Faced with surges in demand due to the pandemic and the ensuing pressure on ICU facilities around the world, both C19_SPACE and CCCTF training programs demonstrated that medical education can be successfully delivered globally and virtually in times of crisis. [76] , [77] The reliance on video conferencing during the pandemic created new opportunities for interface between academic institutions and the broader medical community. Furthermore, e-learning satisfies the need for continuing education and procedural training.…”
Section: Training Agenda In Icmmentioning
confidence: 99%
“…Early on, the ATS developed a COVID-19 resource center, assembled an international expert panel to provide interim guidance on management (as there was no or insufficient evidence), facilitated interactions among division directors across the United States, and distributed a weekly e-mail with updates on the latest breakthroughs and resources, such as the COVID-19 Critical Care Training Forum ( 1 3 ). Furthermore, we formed the Vaccine Working Group and created the Vaccine Resource Center on our website, our assemblies conducted multiple webinars and journal clubs, and the ATS collaborated in joint webinars with our peer societies worldwide.…”
Section: Responding To the Pandemicmentioning
confidence: 99%